Dual-Wavelength Photosensitive Nano-in-Micro Scaffold Regulates Innate and Adaptive Immune Responses for Osteogenesis - Zhao, Qin; Shi, Miusi; Yin, Chengcheng; Zhao, Zifan; Zhang, Jinglun; Wang, Jinyang; Shen, Kailun; Zhang, Lingling; Tang, Hua; Xiao, Yin; Zhang, Yufeng (Nano-Micro Letters, 2020)
The immune response of a biomaterial determines its osteoinductive effect. Although the mechanisms by which some immune cells promote regeneration have been revealed, the biomaterial-induced immune response is a dynamic process involving multiple cells. Currently, it is challenging to accurately regulate the innate and adaptive immune responses to promote osteoinduction in biomaterials. Herein, we investigated the roles of macrophages and dendritic cells (DCs) during the osteoinduction of biphasic calcium phosphate (BCP) scaffolds. We found that osteoinductive BCP directed M2 macrophage polarization and inhibited DC maturation, resulting in low T cell response and efficient osteogenesis. Accordingly, a dual-targeting nano-in-micro scaffold (BCP loaded with gold nanocage, BCP-GNC) was designed to regulate the immune responses of macrophages and DCs. Through a dual-wavelength photosensitive switch, BCP-GNC releases interleukin-4 in the early stage of osteoinduction to target M2 macrophages and then releases dexamethasone in the later stage to target immature DCs, creating a desirable inflammatory environment for osteogenesis. This study demonstrates that biomaterials developed to have specific regulatory capacities for immune cells can be used to control the early inflammatory responses of implanted materials and induce osteogenesis. Highlights: 1 The controlled release of IL-4 and dexamethasone by a dual-wavelength photosensitive nano-in-micro scaffold (biphasic calcium phosphate loaded with goad nanocage, BCP-GNC) enables the regulation of specific immune cells and immune responses. 2 BCP-GNC regulates innate and adaptive immune responses in two stages (directing the M2 polarization of macrophages and inhibiting the maturation of dendritic cells) to promote osteoinduction.